Pengembangan Program Penyebarluasan Produk Pendidikan di SMKS Al Huda Kota Kediri - Fatawi, Rahadian; Latifah, Nur Aini (Efektor, 2020)
For vocational students, the world of work is a desire when stepping on and choosing to continue their studies. It can be said that the majority of vocational students have the same ideals and desires, namely graduating from SMK to get a job. Because it is appropriate for the purpose, education in SMK is designed to create skilled workers who are ready to work for the middle class. So do not be surprised if vocational students have a strong desire to get a job as much as possible after graduating from school. So to help the strong desire of SMK students, it is hoped that they will design a strategy to help market it to the world of business and the world of industry. Where this strategy is expected to be compiled comprehensively and continuously and adapted to the needs of the Business World and the Industrial World. Apart from strategizing, SMK must also build a Business and Industrial Networking in accordance with the Vocational Expertise Program. So, collaboration in developing marketing strategies and building networking with the Business World and the Industrial World is expected that SMK graduates can be absorbed as much as possible in the World of Work.